DAMPAK KARAKTERISTIK DEWAN TERHADAP PROFITABILITAS BANK: Bukti Empiris di Bursa Efek Indonesia - Djoni Djatnika (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2022)
Abstract This study examines the effect of board characteristics on bank profitability with size and growth as control variables. The research was conducted on the Indonesia Stock Exchange for the period 2011-2019. A sample of 300 bank-year observations were analyzed using the PLS SEM method using the Wrap-PLS application. The results show that the size of the board of directors and the proportion of female directors have a positive effect on bank profitability. However, the proportion of independent commissioners has a negative effect on bank profitability. Furthermore, size and growth have a positive effect on bank profitability. Keywords: Board characteristics, bank profitability, control variables.